Macromoths (Erebidae: Lepidoptera) and Geometer Moths (Geometridae: Lepidoptera) Species Diversity in Central Sindh, Pakistan - Zaryab Gul; Mansoor Ali Shah; Naheed Baloach (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Moths are primarily nocturnal, phytophagous, pests of agriculture, night pollinators, and potential bioindicators. The current study is the first to provide information on the diversity, richness, and abundance of moth species in central Sindh, Pakistan. Moths were collected by light traps, light sheets, and insect nets. A total of 517 specimens were collected during four seasons (Winter, Spring, Summer, and Autumn) and sorted out into 2 families. Moreover, Family Erebidae was sorted out into 3 subfamilies (Arctinae, Calpinae, and Erebinae) of 5 genera (Utethesia, Chalciope, Creatonotus, Grammodes, and Eudocima) with 8 species (Utethesia pulchella Linnaeusn1758, Utethesia lotrix Cramer 1789, Chalciope mygdone Cramer 1775, Creatonotus transiens Walker 1855, Grammodes geometrica Fabricius 1775, Grammodes stolida Fabricius 1775, Eudocima phalonia Linnaeus 1763, and Eudocima maternal Linnaeus 1767) while family Geometridae was sorted out into 3 subfamilies (Sterrhinae, Ennominae, and Geometrinae) of 3 genera (Scopula, Isturgia, and Microloxia) with 5 species (Scopula pulchella Fabricius 1794, Scopula minorata Boisduval 1833, Isturgia disputaria Guenee 1858, Isturgia Pulinda Walker 1860, and Microloxia herbaria Hubner 1800). However, the family Erebidae was found to be the most prevalent with 8 species while the family Geometridae was found to be the least prevalent with 5 species. However, the family Geometridae was found to be highest in abundance with 305 specimens while the family Erebidae was found to be lowest in abundance with 212 specimens. According to the localities, the highest value (0.91) of Simpson's index (D) was recorded for Matiari; while the lowest value (0.86) was recorded for Jamshoro. The survey locations featured varied moth fauna, as evidenced by the fact that Matiari was recorded as the highest value (2.394) Shannon index (H) while Jamshoro was recorded as the lowest value (2.034).